La vie intellectuelle des femmes à Beyrouth dans les années 1920 à travers la revue Minerva - Souad Slim; Anne-Laure Dupont (Revue des Mondes Musulmans et de la Méditerranée)
The journal, Minerva, edited from 1923 to 1927, constitutes an useful source for the cultural and intellectual life in Beirut during that period. A journal created by Greek-Orthodox women, Minerva defended both the cause of Arab nationalism as well as the Arab woman, all the while insisting upon her traditional role as an educator, a wife and a mother.